Molecular Modification Strategies for Enhancing CO2 Electroreduction - Yali Wang; Leibing Chen; Guoying Li; Jing Mei; Feng Zhang; Jiaxing Lu; Huan Wang (Molecules, 2025)
Electrocatalytic CO2 reduction reaction (CO2RR) is a crucial technology for achieving carbon cycling and renewable energy conversion, yet it faces challenges such as complex reaction pathways, competition for intermediate adsorption, and low product selectivity. In recent years, molecular modification has emerged as a promising strategy. By adjusting the surface properties of catalysts, molecular modification alters the electronic structure, steric hindrance, promotes the adsorption of reactants, stabilizes intermediates, modifies the hydrophilic–hydrophobic environment, and regulates pH, thereby significantly enhancing the conversion efficiency and selectivity of CO2RR. This paper systematically reviews the modification strategies and mechanisms of molecularly modified materials in CO2RR. By summarizing and analyzing the existing literature, this review provides new perspectives and insights for future research on molecularly modified materials in electrocatalytic CO2 reduction.